Online Digital Photography of Ancient Indonesian Statues for Research Purposes - Sholah, Ahmad Kholdun Ibnu (JANUS, 2023)
During the pandemic, lockdown and closure of facilities limited access to museums and archaeological sites. This condition heavily impacted researcher who require observation for analysis on archaeological object, such as statues. As alternative, photography of statues that is distributed to online platform will certainly help to solve this problem. In this regard, three main topics are presented in this paper. Firstly, a review of studies conducted in the past on ancient Indonesian statues using photography as the main source will be presented showing that photography is able to present a formal dimension of sculpture that is useful for stylistic and iconographic studies. Secondly, an overview of current conditions revealing that a number of museums and institutions have provided digital catalogs containing photographs of ancient Indonesian statues, but they have different policies. Lastly, there are some issues with digitizing photographic resources that require multidisciplinary collaboration to solve. === Selama masa pandemic Covid-19, penghentian kegiatan dan penutupan fasilitas telah membatasi kunjungan ke museum dan situs arkeologi. Keadaan ini sangat berdampak pada peneliti yang harus mengobservasi objek kajiannya, misalnya patung. Sebagai alternatif, foto patung yang disebarluaskan secara daring dapat menjadi solusi masalah ini. Dalam tulisan ini akan dibahas tiga hal terkait hal ini. Pertama, tinjauan terhadap kajian patung kuno di masa lalu yang menggunakan foto sebagai dasar kajian menunjukkan cara itu mampu menyediakan data dimensi bentuk yang amat berguna dalam analisis gaya dan ikonografi. Kedua, kini beberapa museum dan lembaga telah menyebarluaskan katalog digital fotografi patung Indonesia kuno, meskipun kebijakan yang diterapkan beragam.Terakhir, untuk menghadapi berbagai isu digitalisasi sumber kajian berupa fotografi perlu dilakukan kerjasama multidisiplin.